A tiny charge‐scaling in the OPLS‐AA + L‐OPLS force field delivers the realistic dynamics and structure of liquid primary alcohols. Issue 6 (28th December 2021) - Zhang, Xuan; Wang, Yongtao; Yao, Jia; Li, Haoran; Mochizuki, Kenji
Abstract: We carry out molecular dynamics simulations for pure liquid primary alcohols ranging from methanol to 1‐decanol under ambient conditions. Based on the OPLS‐AA force field with the L‐OPLS correction, we demonstrate that a few % increases in the partial charges deliver the realistic dynamics (self‐diffusion coefficient and shear viscosity) and structure (density and X‐ray scattering intensity) as well as enthalpy of vaporization and isothermal compressibility. The validity against thermal expansion coefficient, isobaric heat capacity, and static dielectric constant are also discussed.